Cultural Confidence on "Art & Engineering" Construction of Product Design under "New Liberal Arts". (9th May 2022) - Xu, Lijun; Gao, Jun; Chen, Lu; Liang, Guodong; Feng, Hailong
Abstract : A master's degree program in "new liberal arts" is a great opportunity to strengthen cooperation between art colleges and universities, to promote the construction of product design and digital molding majors, and to promote teaching and research on the "integration" of the theoretical foundations of engineering intelligent manufacturing. To take advantage of cooperative universities' advantageous disciplines and professional platforms, we should construct new art and emerging interdisciplinary majors, as well as promote the construction and exploration of joint training of doctors and masters in relevant disciplines in the interdisciplinary direction of art and engineering. The foregoing approaches are intended to create a new "art and engineering" model for the establishment of a product design speciality at our university. In order to meet the requirements of "Art & Engineering" advocated by the national new engineering construction, art disciplines have their own inherent rules and characteristics. We should actively create disciplinary and professional characteristics, help universities cooperate with each other in high-quality development, and share and win together, in order to continuously achieve new academic results.